Photographic Identification of Tooth Prints After High Temperature Exposure - Khaerunnisa, Rahmadaniah; Oscandar, Fahmi; Syukriani, Yoni (Jurnal Forensik dan Medikolegal Indonesia, 2023)
Tooth prints is a very potential tool in forensic identification as the enamel rod patterns on tooth surface is individually unique. This study was aimed to detect changes of tooth prints after teeth were exposed with high temperatures. Forty-five extracted teeth were divided into 5 groups, then exposed to various high temperatures for 15 minutes in a furnace. To ensure practical application, a highly reproducible digital photographic method to detect tooth prints was developed. Before and after the heating process, tooth prints were photographed. The image data was analysed using an open-source biometric software, and the number of matching points of each tooth was compared before and after treatment. Results showed the decreasing number of match points of tooth prints in accord with the increasing of temperature exposure (P < 0.05). The number of tooth print matching points can be confidently observed at temperatures 600°C or lower. The consistence of matching points shows the prospect of tooth print analysis to become a reliable identification method. This digital photography technique offers a straightforward method for routine dental recording in daily practice by dentists and identification by forensic odontologists. It opens further direction for standardization of pattern analysis, database development, and daily protocols. Keywords: dental photography; forensic identification; high temperature; tooth prints